The level of pivotal thinking among the teaching staff in the College of Basic Education- Department of Mathematics – And its relationship to the achievement of students (Journal of the College of Basic Education, 2019)
The aim of the present research is to identify the level of pivotal thinking among teachers in the Department of Mathematics, College of Basic Education, University of Mustansiriya and its relationship to the achievement of students in mathematics.In order to verify the research objective, the researcher put two hypotheses indicating that there is no statistically significant difference at the level of significance (a = 0.05( between the theoretical average and the arithmetic mean of the teaching degrees in the Department of Mathematics - College of Basic Education at the University of Mustansiriya on the pivotal thinking scale Mathematics.The present research used the descriptive analytical method, the research sample was determined by(16) teachers who are teaching mathematics in the Department of Mathematics, Faculty of Basic Education, University of Mustansiriya, for the academic year 2018-2019.The research found that the teachers in the Department of Mathematics - College of Basic Education at the University of Mustansiriya have a weak level of pivotal thinking; there is a positive and strong correlation between their pivotal thinking skills and their students' achievement in the mathematics subjects they teach them.The researcher recommended trying to develop pivotal thinking skills among their students, and enrich the curriculum of mathematics and other subjects with attitudes that help develop thinking skills. The researcher suggested conducting a follow-up study to reveal the growth of pivotal thinking skills in the student of the stage of the university